Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T20:00:43+01:00
25m3 -26m3=-1m³
6,5ac - 6,5ca=0
7,24mp-6,94mp=0,3mp
14b2ac2-6c2ab2=8ab²c²
m4-7m4+9m4=3m⁴
16,25-7x+5 1/4(jedna czwarta) x =16,25-1,75x
-2 x2 -3 x2 - 4 x2 - 5 x2= -14x²
2010-02-23T20:04:37+01:00
25m3 -26m3=m3(25-26)
6,5ac - 6,5ca=6,5ac(1-1)
7,24mp-6,94mp=mp(7,24-6,94)
14b2ac2-6c2ab2=2ab2c2(8-3)
m4-7m4+9m4=m4(1-7+9)
16,25-7x+5 1/4(jedna czwarta) x =16,25-x(7-5 1/4)
-2 x2 -3 x2 - 4 x2 - 5 x2= x2=(-2-3-4-5)
2010-02-23T20:05:28+01:00
25m3 -26m3= -1m3
6,5ac - 6,5ca= 0
7,24mp-6,94mp= 0,3mp
14b2ac2-6c2ab2= 8b2ac2
m4-7m4+9m4= 3m4
16,25-7x+5 1/4(jedna czwarta) x = 16,25-1,75x
-2 x2 -3 x2 - 4 x2 - 5 x2= -14x2